The Correlation Between Mothers’s Attitude And The Role Of Midwife With Babies And Toddlers Participation On National Childhood Immunization Month Program (Bian) In Selaawi Village Sukaraja District Sukabumi Regency 2022 - Rizki, Fathia; Maria Mayangsari; Liawati (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Immunization is the most cost-effective effort in reducing morbidity and mortality from diseases that can be prevented by immunization. To find out the relationship between mother's attitude and midwife's role with the participation of infants and toddlers in the BIAN program in Selaawi Village, Sukaraja District, Sukabumi Regency in 2022. Correlative descriptive research design with a cross-sectional approach. The research variables were the mother's attitude, the role of the midwife, and the participation of toddlers in the BIAN program. The research sample was 231 mothers of babies/toddlers in Selaawi Village in December 2022, using stratified random sampling. The research instrument was a questionnaire on mother's attitude, midwife's role, and BIAN participation data. Half of the babies/toddlers in Selaawi Village did not participate in the BIAN program (50.2%), most of the mothers had a negative attitude towards immunization (42.2%), and thought that midwives had little role in immunization (43.3%). There was no significant relationship between mother's attitude and infant/toddler participation in the BIAN program (p=0.210). There is a significant relationship between the role of the midwife and the participation of infants/toddlers in the BIAN program (p=0.029). There is no relationship between mother's attitude and the participation of babies and toddlers in the BIAN program in Selaawi Village, Sukabumi Regency in 2022. There is a relationship between the role of midwives and the participation of babies and toddlers in the BIAN program in Selaawi Village, Sukabumi Regency in 2022. It is recommended to study and conduct research in a wider scope so that the research results can be more generalized to a wider population.